Potoczna i naukowa kategoryzacja świata a poetyckie transgresje (na przykładzie kilku wierszy Wisławy Szymborskiej) - Szczepankowska, Irena (Stylistyka, 2023)
Acquiring a knowledge that goes beyond sensual experience (for example, looking through a microscope or telescope) and beyond categories rooted in language, reąuires a lot of courage, Crossing the safe boundaries of the domesticated and designated world. The poetic porte-parole of Wisława Szymborska struggles with the experience of Crossing these boundaries, which leads to undermining the customary categorisations established in our common language. The author of the paper interprets these poetic transgressions - evoked in the works of the Noble Prize winner - from the linguistic perspective. Namely, she refers them to two concepts of the linguistic categorisation of the world: logical (scientific), originat- ing from Aristotle’s theory, and cognitive, alluding to Immanuel Kant’s philosophy fo- cused on the popular (nai’ve and culturally determined) image of the world. The paper presents the manner in which devices of artistic expression, such as a metaphor, nega- tion, tautology, gradation, etc., are adopted by the poet to undermine both the popular (stereotypical) qualification of phenomena and scientifically determined category boundaries.